Knowing and Experiencing the Practice of Teaching Journey towards Becoming a Critically Reflective Teacher - Bose, Nitika (JOURNAL OF INDIAN EDUCATION, 2018)
Pivotal to teacher development is the practice of reflection and therefore, its importance in a Teacher Education programme cannot be undermined. Unless teachers foster the practice of critical reflection, they remain engulfed in parochial values, unexamined assumptions and biases, and prejudices emanating due to unquestioned judgments and interpretations. The present article explores the student Teacher’s experiences while pursuing Bachelors of Education (B.Ed.) programme, to understand the ways in which reflective practices nurture their professional identity as teachers. Data were collected from observations, personal diaries, reflective journals and narrative accounts of student teachers. An analytic framework of Dewey and Schön were used to interpret the narratives of the student teachers. It was found that the professional knowledge of teachers was intricately linked to what teachers thought and experienced before and while teaching. Also, evidence from the narrative accounts illustrated the student-teacher’s capabilities to learn, and the ways in which they were able to construct meaning by interrelating the practice of teaching to their own life experiences. They were thus able to extend reflective learning beyond themselves to wider group of individuals. The article therefore highlights the relevance of reflections as an integral part of preservice Teacher Education, enabling critical self-awareness and informed educational practices.